The Nexus Between GDP and Military Expenditure in Indonesia: Evidence From Time Series Analysis - Rasyid, Muhammad Gilang (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
As one of the key players in the region, Indonesia remains unable to fulfill its full potential in the defense sector. Indonesia's consistently low military expenditure has impeded the country's modernization program intended to be achieved in 2024 and might hinders in achieving the ideal defense posture in 2045. Therefore, analyzing the determinants of military spending and their effect to understand its potential in the face of such a problem is crucial. This study investigates the long-run multiplier (LRM) of a key determinant of military expenditure, namely Gross Domestic Product (GDP), in a dynamic time series model using the Generalized Error Correction Model from 1974 to 2016. Additionally, a novel LRM-bounds testing approach is employed to assess the long-run relationship. The findings reveal that a 1% increase in GDP leads to approximately 0.3% on average increase immediately and a cumulative increase of 0.4% over the next six years. From this result, Indonesia should strive for consistent and strong economic growth. This is because a large increase in GDP has a multiplier effect that will be beneficial for Indonesia's military spending. Therefore, even if defense spending as a share of GDP remains minimal, the problem can be minimized by strong GDP growth. While strong GDP growth might have a beneficial impact on military spending, this article also emphasizes the importance of effectively utilizing defense expenditure by strategically allocating more resources toward arms acquisition, research, and the development of the defense industry. Finally, since social processes rarely rest, policymakers should also consider temporal dynamics when dealing with GDP and military expenditure.